Sistem Pakar Diagnosa Penyakit Bakteri Staphylococcus Dengan Menggunakan Metode Dampster Shafer: Sistem Pakar Diagnosa Penyakit Bakteri Staphylococcus Dengan Menggunakan Metode Dampster Shafer - Ayu Prima Siska (Perkumpulan Doktor Indonesia Maju (PDIM), 2021)
Staphylococcus is one of the most common bacteria that causes infection in the world. This is because many people do not know the symptoms of staphylococcus bacteria. Symptoms in staphylococcal bacteria vary so often that they are only considered a complaint due to lifestyle. This makes the disease in staphylococcus bacteria ignored and undiagnosed so it is too late to be treated. In this study, the authors made an application of the Dempster Shafer method to the expert system of diagnosing disease in Staphylococcus bacteria by giving value to each symptom obtained from an expert. All values ​​obtained will be resolved using the Dempster Shafer formula. This expert system is quite easy to use, only by giving a sign of the symptoms that are felt it will come out the results of the diagnosis of the disease. Thus the community can find out what diseases are suffered as well as solutions to handling the disease based on the disease experienced.